Evaluation of the awareness and utilization of oral rehydration salt and zinc in managing diarrhoea among under-five children in Oyo State, Nigeria - Fagbamigbe, Adeniyi Francis; Joseph, Juma; Odongo, Alfred Owino; Mogere, Dominic; Kariuki, John (International Journal Of Community Medicine And Public Health, 2022)
Background: Nigeria ranks as one of the countries with the highest negative consequences of diarrhoea in sub-Saharan Africa. The aim of the study was to evaluate the awareness and utilization of ORS and zinc in managing diarrhoea among under-five children (U5C) in Oyo state, Nigeria. Methods: Data was obtained from a cross-sectional survey (n=1154) as well as focus group discussions among mothers/caregivers of U5C and key informant interviews in Oyo state. Descriptive, bivariate and multivariate logistic regression analyses were performed. Results: Nine of every ten caregivers were aware of the use of ORS/zinc for managing diarrhoea cases. Prevalence of ever-use of ORS/zinc for managing diarrhoea cases was 5.4% while the prevalence of having diarrhoea recently was 6.2% (71/1154). Of the 71 mothers whose U5C recently had diarrhoea, 41 (57.7%) used ORS/zinc to manage a recent episode of diarrhoea. Adjusted odds of using ORS/zinc to manage diarrhoea was 2.64 (aOR=2.64; 95%CI: 1.18-10.27 times higher among children who are the first births than those with fourth or higher birth order. The adjusted odds of using ORS/zinc to manage diarrhoea was 9 times (aOR= 9.15; 95%CI: 1.99-34.47) higher among mothers aged 20 to 24 years than those aged 30 to 39 years. Conclusions: Despite the high level of awareness of use of ORS and zinc in managing diarrhoea, ever-utilization is low but recent use by three-fifths of caregivers is fair. There is a need for Oyo state ministry of health and other stakeholders to promote the use of ORS and zinc in managing diarrhoea.